Biosynthesis of ZnO nanoparticles using Hagenia abyssinica leaf extracts; their photocatalytic and antibacterial activities. Issue 1 (31st December 2022) - Zewde, Dagme; Geremew, Belete
ABSTRACT: This study investigates the green synthesis of ZnO NPs using an aqueous solution of hagenia abyssinica leaf extract, which acts as a reduction of zinc acetate dihydrate as a reducing agent and stabilizing agent. The synthesized ZnO NPs were characterized by various techniques such as XRD, SEM, FTIR, and UV–Vis spectroscopy. The XRD pattern confirmed that the hexagonal crystalline phase structure and average crystal size of the synthesized nanoparticle was 27.833 nm. Several functional groups were detected using the Fourier transform infrared (FTIR) method. Within 120 minutes of sunlight irradiation, 83.17% photocatalytic degradation of MO was recorded, with an initial concentration of 15 ppm and a catalyst dosage of 40 mg. The present study shows a novel, eco-friendly method to synthesize zinc oxide nanoparticles that have potential applications in water treatment and dye degradation. The disc diffusion method was used to determine antibacterial activity against gram-positive ( S. aureus and S. epidermidis ) and gram-negative ( E. coli and K. pneumoniae ) bacterial strains. The biosynthesized ZnO nanoparticles were highly effective against S. epidermidis with inhibition zones of 21 ± 1.0 mm at 30 mg/mL and less effective against E. coli with inhibition zones of 16 ± 1.0 mm at 10 mg/mL.